Preceramic Mesoamerica
1 online resource (xxviii, 571 pages)
Keywords: "Preceramic Mesoamerica delivers cutting-edge research on the Mesoamerican Paleoindian and Archaic periods. Chapters address a series of fundamental questions in American archaeology including the peopling of the Americas, human adaptations to late glacial landscapes, the Neolithic transition, and the origins of sedentism and early village life. This volume presents innovative and previously unpublished research on the Paleoindian and Archaic periods and evaluates current models in light of new findings. Examples include breakthroughs in dating Mesoamerica's earliest sites and their implications for models of hemispheric colonization; the transition to postglacial patterns of settlement and subsistence; divergent pathways to initial sedentism; the possibility of Archaic-period monumentality; changing patterns of interregional exchange and interaction; and debates surrounding the origins of agriculture, ceramics, and full-time village life. The volume provides a new perspective on the Mesoamerican Preceramic for students and scholars in archaeology, anthropology, and history. Readers will come to understand how the Preceramic contributed to the emergence of the cultural traditions that anthropologists recognize as Mesoamerica"--